EFFECTS OF LATIHAN PASRAH DIRI ON THE IMPROVEMENT OF DEPRESSIVE SYMPTOMS - Hamra, Muhammad Yusuf; Sumardi, Sumardi; Siswanto, Agus; Sofia, Noor Asyiqah (Acta Interna The Journal of Internal Medicine, 2011)
ABSTRACTBackground. Depression is more common in persons with chronic illnesses such as diabetes, epilepsy and infection of Human Immunodeficiency Virus (HIV). Depression can make HIV worse. Antidepressant may need, but there can be interaction and side effect when use Antiretroviral (ARV) and antidepressant in combination. Complementary and alternative medicine (CAM) include Latihan Pasrah Diri(LPD) may seem safe to treat depression in HIV patient.Methods. This is a quasi experimental study, participant include outpatient dan inpatient at RSUP Dr. Sardjito, Yogyakarta. They were aged >18 years. After scoring with Zung Self Rating Scale for depression, participants allocated into two groups, with dan without Latihan Pasrah Diri program. Zung Self Rating Scale for depression was evaluated after 1 cycle of program.Result. The means of Zung Self-Rating Depression Scale score before and after LPD were 42,21 ± 9,3 and 35 ± 10,73 (p 0,003). While in control group (without LPD / brief psychotherapy) the means of Zung Self-Rating Depression Scale score before and 3 weeks after brief psychotherapy were 42,93 ± 7.45 and 39,36 ± 7,69 (p 0,019). Statistically there was no significancy in the means of delta Zung Self-Rating Depression Scale in LPD group and control group.Conclusion. It was concluded from this study that there is an influence on the improvement of depressive symptoms post- Latihan Pasrah Diri program to people with HIV / AIDS. Key words: depression, HIV, Latihan Pasrah Diri, Zung Self-Rating Scale